The effect of different psychological interventions on athletes` competitive anxiety: A systematic review and bayesian network meta-analysis - Li, L.; Wang, J.; Li, Q.; Fu, Q. (Sports Medicine - Open, 2026)
Background Competitive anxiety is a common psychological challenge among athletes and can negatively affect sports performance. Although several psychological interventions have been shown to reduce competitive anxiety, their relative effectiveness has not been well established. This study aimed to compare the effectiveness of different psychological interventions in reducing competitive anxiety in athletes.